2013
DOI: 10.1530/joe-13-0240
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and photoperiod modulate pubertal development in Atlantic salmon (Salmo salar)

Abstract: The Atlantic salmon shows substantial life cycle plasticity, which also applies to the timing of puberty. While it is characterized by the activation of the brain-pituitary-gonad axis, many morphophysiological aspects of puberty and the influence of environmental conditions, such as water salinity, are not well understood in fish. Here, 12-month-old Atlantic salmon coming from an out-of-season smoltification regime in December were exposed to freshwater (FW) or seawater (SW) at 16 8C to stimulate puberty under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 50 publications
8
75
1
Order By: Relevance
“…As in all vertebrates, puberty in fish is governed by the hypothalamus-pituitary-gonad (HPG) axis and is marked by an increased production of gonadotropins (follicle stimulating hormone, FSH; luteinizing hormone, LH) in the pituitary (Chen and Ge, 2012). The timing of puberty is different for different fish species and is influenced by age, size and environmental cues Ge, 2012, 2013;Melo et al, 2014). However, it has been shown that treatment with androgenic steroids can advance the timing of puberty, both with regard to gonadotropin production and gonad maturation (Antonopoulou et al, 1995;Antonopoulou et al, 1999;Melo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in all vertebrates, puberty in fish is governed by the hypothalamus-pituitary-gonad (HPG) axis and is marked by an increased production of gonadotropins (follicle stimulating hormone, FSH; luteinizing hormone, LH) in the pituitary (Chen and Ge, 2012). The timing of puberty is different for different fish species and is influenced by age, size and environmental cues Ge, 2012, 2013;Melo et al, 2014). However, it has been shown that treatment with androgenic steroids can advance the timing of puberty, both with regard to gonadotropin production and gonad maturation (Antonopoulou et al, 1995;Antonopoulou et al, 1999;Melo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The timing of puberty is different for different fish species and is influenced by age, size and environmental cues Ge, 2012, 2013;Melo et al, 2014). However, it has been shown that treatment with androgenic steroids can advance the timing of puberty, both with regard to gonadotropin production and gonad maturation (Antonopoulou et al, 1995;Antonopoulou et al, 1999;Melo et al, 2014). There are also several pieces of evidence suggesting that EDCs could be involved in the decreased age of pubertal onset observed in humans over the last decades (Parent et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The timing of maturation events in Atlantic salmon has been linked to physical condition and could possibly be connected to certain set-points or ratios of lipid and protein mass (Thorpe et al, 1990, Thorpe et al, 1998 interacting with external cues, and in particular photoperiod, for initiation of sexual maturation (Melo et al, 2014, Andersson et al, 2013, Benedet et al, 2010, Vikingstad et al, 2008. The high plasticity of salmon seems to allow for specific time windows (signaled through photoperiod) during which the salmon can initiate the sexual maturation process or wait depending on body condition and ambient circumstances (Thorpe et al, 1990, Thorpe et al, 1998.…”
Section: Environmental Factors and External Cues And Their Effect On mentioning
confidence: 99%
“…Many studies have shown the effect of exposure to artificial light/dark cycles on the onset of maturation; hereby opening an opportunity to postpone maturation by keeping the fish under a light regime not providing photoperiodic cues that could induce maturation (Adams and Thorpe, 1989, Taranger et al, 1998, Porter et al, 1999, Melo et al, 2014. In a study by Porter et al (1999) only 6.1% matured under an artificial light regime (exposed to additional light during night) compared to 61.5% maturing in the control group exposed to the natural light regime.…”
Section: Effect Of Photoperiod Manipulation On Maturationmentioning
confidence: 99%
See 1 more Smart Citation